PROTOCOL: Case management interventions seeking to counter radicalisation to violence: A systematic review of tools and approaches. Issue 1 (5th February 2023) - Lewis, James; Marsden, Sarah; Cherney, Adrian; Zeuthen, Martine; Bélanger, Jocelyn J.; Zubareva, Anastasiia; Brandsch, Jürgen; Lubrano, Mauro
Abstract: This systematic review consists of two parts. Part I seeks to synthesise evidence from primary or secondary research studies examining the implementation and effectiveness of case management tools and approaches currently being used to counter radicalisation to violence. Part II is an 'overview of reviews' that seeks to identify relevant and transferable lessons from systematic reviews and meta‐analyses of case management tools and approaches used in the broader field of violence prevention that could be applied to counter‐radicalisation practice.